Quality Analysis of Islamic Education Problem Based on Higher Order Thinking Skill Class V SDS Budi Mulia Medan - Ali Imran Sinaga; Salamuddin; Alnida Azty (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2020)
The purpose of this study was to analyze the theoretical quality of the subjects of Islamic Education class V SDS Budi Mulia is based on Higher Order Thinking Skill (HOTS) based on aspects of material, construction, language and based on HOTS based on Bloom's Taxonomy of cognitive domains. This research was conducted at SDS Budi Mulia Medan Tanjung Mulia Hilir District Medan North Sumatra Province and the subject and object of research are Islamic Education teacher class V and Islamic Education questions in semester I Class V. The research method used is to use a qualitative approach and use the instrument of semester I Islamic Education questions and interviews with Islamic Education teachers to theoretically analyze the quality of items based on material, construction and language aspects and based on quality analysis of HOTS-based items. The results of the study of 35 multiple choice questions obtained the following results: (1) based on the analysis of the item quality aspects of the material feasibility of 91.42% (32 questions) worth using, there are some questions that do not meet the criteria such as material that is not in accordance with the composition, answer choices which is not homogeneous and logical and the existence of questions that do not have the answer key, (2) based on the analysis of the quality of the aspects of the construction feasibility of 88.57% (31 questions) are suitable to be used, there are some questions that do not meet the criteria such as the subject still gives clues to the answer key and the length of the choice of money answers are not the same, (3) based on the analysis of items about the aspect of language worthiness of 42.85% (20 questions) worth using, there are some questions that do not meet the criteria such as using language that is not in accordance with Indonesian language rules, and the choice of answers repeat the same word / group of words, and (4) Based on an analysis of the quality of items according to the Bloom domain's taxonomy cognitive can be concluded from 35 multiple choice questions obtained that there are 17 questions (48.6%) including the LOTS questions category with details C1 (remembering) = 8 questions (22.8%), C2 (understanding) = 3 questions (8 , 7%), C3 (applying) = 6 questions (17.1%). While the rest included in the HOTS questions category, however all of them were in the C4 criteria (Analysis) = 18 questions (51.4%) while none of the questions were in C5 and C6.